Variations des caractères biométriques et des constitutants biochimiques d'une population C. gigas (Thunberg) d'un parc d'élevage du bassin de Marennes - Oléron en 1974 - Gras, Marie-paule; Gras, Paul (Symposium CIEM, held in Aarhus, 9-12 july 1975, Danemark, 1975)
At the beginning of its introduction, following the massive mortality rate of 1970-1971 that struck the Portuguese oyster, Crassostrea angulata (COMPS and GRAS 1973), the oyster from the Pacific, Crassostrea gigas, displayed excellent growth in addition to exceptional hardiness and resistance to mortality. But, since 1973, in most of the farming areas, there has been a slowdown in the growth of the oysters and an at times quite pronounced decrease in their quality. It was in order to better understand their adaptation to the environment and the causes of the lowering of their growth rate and their condition that a study was undertaken in 1974, in one of the largest areas of flat cultivation of the Marennes-Oléron basin, located on the east coast of the Isle of Oléron. Au début de son implantation, consécutive à la mortalité massive de 1910-1971 qui frappa l'huître portugaise Crassostrea angulata (COMPS et GRAS 1973), l'huître du Pacifique Crassostrea gigas a montré, en plus d'une rigueur et d'une résistance exceptionnelles à la mortalité, une excellente croissance. Mais, depuis 1973, on constate dans la plupart des zone d'élevage un ralentissement de la pousse des huîtres et une diminution parfois accusée de leur qualité. C'est afin de mieux connaître leur adaptation au milieu et les causes de l'abaissement du taux de croissance et de leur condition qu'une étude fut entreprise en 1974, dans une des plus importantes• zones de culture à plat du bassin de Marennes-Oléron, située sur la Côte Est de l'Ile d'Oléron•